Kinetics of Oxidation of L-Cysteine by Transition Metal Complexes - M. Abdel-Halim, Hamzeh; S. Abu-Surrah, Adnan; E. Qaqish, Shatha (Asian Journal of Chemistry, 2010)
Kinetics of the oxidation of L-cysteine by chromium(III), manganese(III), iron(III), and cobalt(III) complexes of amine, 2,2´-bipyridine, ethylenediamine, acetylacetonate, N,N´-bis(salicylidine)-1,2-ethylenediamine and (1R, 2R)-(-)-N,N´-bis(3,5-di-t-butyl-salicylidene)-1,2-cyclohexyldiamine> have been studied spectrophotometrically. Kinetics measurements were run under pseudo-first order conditions in which the concentration of cysteine is between one and two orders of magnitude greater than that of the transition metal complex. Measurements were done in aqueous and water ethanol solutions at 25ºC, pH = 7 and an ionic strength of 0.20 M. The orders of the reaction with respect to both cysteine and the transition metal complex were determined. The observed rate constants and the overall rate constants were measured. It is found that the rate of oxidation depends on the metal centre and on the geometry of the complex. It also depends on the nature of the ligand, related to its degree of conjugation, number of coordination sites, size and strength in the spectrochemical series. The effect of the solvent and other variables on the rate of the reaction were studied and discussed.